A Comparative Study of Premonsoon and Postmonsoon Status of Different Physical and Chemical Parameters of Water Samples Collected From the Various Sources of Water in Todaraisingh Tehsil of Tonk (Raja (Global Journal of Science Frontier Research, 2013)
Contamination of ground water with fluoride is due to the naturally fluoride rich rock salt system. Hence almost all the area is fluorosis prone.
Keywords: premonsoon; postmonsoon; concentration of ions; fluoride; fluorosis; water quality standards; water quality parameters